Pengaruh Kombinasi Teh Kompos Berbahan Dasar Ekskreta Ayam dan Biochar Berbahan Dasar Sufmuti (Chromolaena odorata L.) terhadap Pertumbuhan dan Produksi Rumput Odot (Pennisetum purpureum cv. Mott) - Yustina Suri (JAS, 2021)
The purpose of this study was to determine the effect of biochar level and compost tea dosage and the interaction between the factors on the growth and production of odot grass. This research was conducted from 25 May 2020 to 3 August 2020 at the experimental garden of the Faculty of Agriculture, University of Timor, Sasi Village, Kota District, North Central Timor Regency. The method used in this research is the experimental method using a completely randomized design (CRD) 3x3 factorial pattern. The factors tested were the first factor, the level of biochar and the second, the dose of compost tea. Biochar level consists of 3 levels including: L0: Without Biochar, L1 : Biochar 100 g / pot, L2 : Biochar 200 g / pot. The second factor consists of 3 levels of compost tea, including D0: Without Compost Tea, D1 : 150 ml / pot dose, D2 : 300 ml / pot dose. From the two factors above, 9 treatment combinations were produced consisting of L0D0, L0D1, L0D2, L1D0, L1D1, L1D2, L2D0, L2D1, L2D2 and each combination consisted of 4 replications so that there were 36 experimental units. The variables observed were plant height (cm), number of tillers (shoots), stem diameter, leaf fresh weight (g), leaf dry weight (g). Results showed that there was no interaction between biochar level and compost tea dose on plant height, stem diameter, number of tillers, fresh weight and dry weight of odot grass leaves. It was concluded that the best crop production was produced by the combination treatment of 200 g/pot of biochar and 300 ml/pot of compost tea and there was no interaction between biochar level and compost tea dose on growth and production of odot grass. Giving Biochar with a level of 200 g (L2) significantly (P<0.05) was able to increase the production of fresh weight by 66.40 g and plant dry weight by 29.10 g, but had no significant effect (P>0.05) on plant height, stem diameter and number of tillers generated. Giving a dose of 150 ml compost tea (D1) gave the best results on the resulting stem diameter of 1.27 cm but had no effect on other variables.